2011
DOI: 10.1158/1535-7163.mct-11-0202
|View full text |Cite
|
Sign up to set email alerts
|

Differential Expression of Uridine Phosphorylase in Tumors Contributes to an Improved Fluoropyrimidine Therapeutic Activity

Abstract: Abrogation of uridine phosphorylase (UPase) leads to abnormalities in pyrimidine metabolism and host protection against 5-fluorouracil (5-FU) toxicity. We elucidated the effects on the metabolism and antitumor efficacy of 5-FU and Capecitabine in our UPase knockout (UPase −/−) model. Treatment with 5-FU (85 mg/kg) or Capecitabine (1000 mg/kg) 5 days a week for 4 weeks caused severe toxicity and structural damage to the intestines of wild-type (WT) mice, but not in UPase −/− animals. Capecitabine treatment resu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 34 publications
(49 reference statements)
0
11
0
Order By: Relevance
“…Uridine-induced DNA damage was also confirmed in multiple cell lines (48). Interestingly, tissue uridine levels have been implicated as being protective of 5-FU-induced damage in the colon (49), and AA experience fewer gastrointestinal side effects in response to 5-FU, leading to the hypothesis that AA might have higher colonic uridine levels. Taken together, these findings provide rationale for further investigation of inter-ethnic differences in 1α,25(OH) 2 D 3 regulation of UPP1 , uridine homeostasis and DNA damage in the colon.…”
Section: Discussionmentioning
confidence: 99%
“…Uridine-induced DNA damage was also confirmed in multiple cell lines (48). Interestingly, tissue uridine levels have been implicated as being protective of 5-FU-induced damage in the colon (49), and AA experience fewer gastrointestinal side effects in response to 5-FU, leading to the hypothesis that AA might have higher colonic uridine levels. Taken together, these findings provide rationale for further investigation of inter-ethnic differences in 1α,25(OH) 2 D 3 regulation of UPP1 , uridine homeostasis and DNA damage in the colon.…”
Section: Discussionmentioning
confidence: 99%
“…The first 2 steps take place primarily in the liver, while the 3 rd and final step is catalyzed by thymidine phosphorylase (TP) and uridine phosphorylase (UP) [45–48], and this occurs in both normal and tumor tissue. It has been shown that both TP and UP are expressed at higher levels within tumor tissue when compared to normal tissue, thereby leading to preferential conversion to 5-FU in tumor tissue with decreased systemic 5-FU exposure [49].…”
Section: -Fu Tdm With Capecitabinementioning
confidence: 99%
“…UPase Ϫ / Ϫ mice with genetic deletion of UPP1 gene exhibited a 6-fold increase and a 3-fold increase in the plasma and liver uridine concentration, respectively ( 15,16 ). In this study, we generate a transgenic UPase1 -TG mouse strain with genetic knock-in of mouse UPP1 gene.…”
Section: Screening For the Effects Of Inhibitors And Intermediates Ofmentioning
confidence: 99%